A Bioinformatics-Based Evolutionary Analysis On Southeast Asia H1n1 Influenza Virus Strains - Teh, Ban Hong (2013)
Influenza virus A (H1N1) is known to be the causative agent of severe influenza infections worldwide. In April 2009, a pandemic outbreak of influenza disease had occurred for the first time in 21st century. To date, vaccination and antiviral drugs are the only effective treatments to combat influenza infection. Thus, understanding the evolution of influenza virus A (H1N1) within Southeast Asia (SEA) region is crucial to better understand about the diversification, emergence, resistance and the vaccine efficacy. In order to gain insight into the matter, phylogenetic analyses were conducted on the full-length amino acid sequences of hemagglutinin (HA), neuraminidase (NA) and matrix protein 2 (M2) of influenza virus A (H1N1) obtained from SEA. Based on the phylogenetic analysis, cocirculation of both seasonal and pandemic strains were observed and identified via the segregation of sequences into two different clades. The results had revealed that sequences clustered in A/California/07/2009-like clade were the dominant influenza strains for the 2009 pandemic occurrence in SEA. In addition, phylogenetic analyses for HA, NA and M2 showed they were related to the vaccine strains for the 2009- 2011 influenza seasons, with an average of 96.5%, 98.1% and 96.9% sequence identity, respectively. The most notable differences are three amino acid substitutions (P100S, S220T and I338V) in almost all HA while two amino acid substitutions (V106I and N248D) in all NA of influenza A (H1N1) pandemic viruses in SEA.